Effects of lisuride hydrogen maleate on pericontusional tissue metabolism, brain edema formation, and contusion volume development after experimental traumatic brain injury in rats - Zweckberger, Klaus; Simunovic, Filip; Kiening, Karl; Unterberg, Andreas; Sakowitz, Oliver (Neuroscience letters, 2011)
After traumatic brain injury (TBI), the primary insult is followed by a cascade of secondary events which lead to enlargement of the primary lesion and are potentially amenable to therapeutic intervention. Lisuride is a dopaminergic agonist with additional serotoninergic, adrenergic, and glutamate antagonistic properties. In lack of previous data on lisuride in TBI, and based on well documented changes of dopamine metabolism after TBI, we speculated that lisuride could provide neuroprotection in the acute and post-acute stage of controlled cortical impact (CCI) injury in rats. The effect of varying dosages of lisuride on physiological parameter was investigated. Cerebral microdialysis (CMD) was employed to provide a temporal profile of lactate, pyruvate, glucose and glutamate in the pericontusional brain tissue. Additionally, brain edema formation and the development of contusion volume were assessed. In this study, no effect of treatment was seen on physiological parameters or microdialysis profiling of tissue metabolites. Whereas posttraumatic increase in brain water content and an increase in contusion volume could be observed, there was no significant effect of treatment. Taken together, our results suggest that lisuride does not provide neuroprotection in the CCI model at the acute and subacute stages. Based on the available literature, however, it might be possible that dopamine agonists such as lisuride, respectively, improve outcome in terms of cognitive function in a chronic setting.
Gesehen am 30.01.2023